A single machine scheduling problem with machine availability constraints and preventive maintenance. Issue 9 (3rd May 2021) - Chen, Lu; Wang, Jinfeng; Yang, Wenhui
Abstract : Considering the impact of machine availability is essential in production scheduling, especially when the target is to minimise total tardiness. In this study, a single machine scheduling problem derived from a rotor production workshop is addressed. We evaluate machine availability by its reliability, which can be restored by preventive maintenance (PM). PM with different improvement effectiveness is considered in the problem formulation. A genetic algorithm (GA) is developed to solve the problem. Emmons dominance rules are applied in the mutation processes of the GA. Computational experiments demonstrate the effectiveness and efficiency of the algorithm. Sensitivity analyses have been conducted to provide useful managerial insights for real workshop scheduling.